Human Carbon Footprint as the Basis for Determining Healthy Indoor Volume Dimensions - Harida Samudro; Sarwoko Mangkoedihardjo (Institute of Medico-legal Publications Pvt Ltd, 2021)
This paper was presented to determine the volume unit of indoor based on the human carbon footprint. Thepurpose of this approach was to formulate the ideal dimensions of an indoor, which was able to maintainhuman health. The basis for determining the dimensions was adapted to tropical conditions. For users innon-tropical areas, slight adjustments to temperature and ventilation may be required.Some examples ofindoor dimension evaluation and planning were presented in this paper. In general, it was obtained that theindoor dimension could be found using the volume unit of a healthy room of3.0 m3/person/hour. The volumeunit was linear with the number of users and time of existence in the room. This contributed significantly topeople, who can easily and quickly find out the dimensions of space according to their needs.